Prevalence, Treatment, and Associated Factors of Hypertension in Spain: A Comparative Study between Populations. (14th August 2018) - Corbatón-Anchuelo, Arturo; Martínez-Larrad, María Teresa; Prado-González, Náyade del; Fernández-Pérez, Cristina; Gabriel, Rafael; Serrano-Ríos, Manuel
Abstract : The prevalence and related factors of hypertensive subjects according to the resident area (rural versus urban) were investigated in two population-based studies from Spain. Medical questionnaires were administered and anthropometrics were measured, using standardized protocols. Hypertension was diagnosed in pharmacology treated subjects or those with blood pressure (BP) ≥140/90 mm Hg. Regarding BP control, it was defined as under control if BP was <140/90 or <140/85 mm Hg in type 2 diabetic subjects. Information on educational status, social class, smoking habit, and alcohol intake was obtained. 3, 816 subjects (54.38 % women) were included. Prevalence of diagnosed hypertension was higher in women and showed no differences according to the living area (men: urban 21.88 versus rural 21.92 %, p = 0.986; women: urban 28.73 versus rural 30.01 %, p = 0.540). Women living in rural areas and men with secondary or tertiary education levels had a lower probability of being BP uncontrolled (OR (95 % CI): 0.501 (0.258–0.970)/p=0.040, 0.245 (0.092–0.654)/p=0.005, and 0.156 (0.044–0.549)/p=0.004, respectively). Urban young men (31-45 years) and medium aged women (46-60 years) were less BP controlled than their rural counterparts (41.30 versus 65.79 %/p=0.025 and 35.24 versus 53.27 %/p=0.002, respectively).